Investigation Study of the Influence of Pole Numbers on Torque Density and Flux-Weakening Ability of Fractional Slot Concentrated Winding Wheel-Hub Machines - Zichong Zhu; Yunkai Huang; Jianning Dong; Fei Peng (IEEE Access, 2019)
Fractional slot concentrated winding machines (FSCWMs) with the low operation speed and large diameter usually have a large number of poles and slots; thus, numerous pole/slot combinations are feasible. The common practice to choose pole/slot combinations by multiplying the basic combinations may neglect some competitive candidates. Taking 36-slot FSCWMs as examples, this paper investigates the influence of pole numbers on torque density and flux-weakening ability, the two most vital performances of wheel-hub machine. It is shown that the machines with pole number slightly less than the slot number have the highest torque densities. Each component of synchronous inductance is separately analyzed, and its variation against pole numbers shows obvious regularity. Machines with pole numbers larger than the slot numbers have an excellent flux-weakening ability due to the large inductance and small permanent magnet flux linkage. The measurements together with the finite element analysis results confirm that the stator leakage inductance contributes the most to the superior flux-weakening ability. The identical analysis is also performed on 54-slot and 81-slot FSCWMs, with similar regularities observed.